An immunomics approach for the analysis of natural antibody responses to Plasmodium vivax infection1. Issue 8 (14th August 2015) - Chen, Jun-Hu; Chen, Shen-Bo; Wang, Yue; Ju, Chuan; Zhang, Ting; Xu, Bin; Shen, Hai-Mo; Mo, Xiao-Jin; Molina, Douglas M.; Eng, Michael; Liang, Xiaowu; Gardner, Malcolm J.; et al.
<x xml:space="preserve">Abstract</x> Plasmodium antigens identified by proteome microarrays provide the clues for understanding host immune response to Plasmodium vivax infection.